LITERATURE REVIEW STUDENT'S METACOGNITIVE ABILITY: BIBLIOMETRIC ANALYSIS - Ermia Fadilata Khoir; Nadi Suprapto; Woro Setyarsih; Utama Alan Deta (Journal of Teaching and Learning Physics, 2022)
This study aims to determine the relationship between scientific literacy and students' metacognitive abilities. The research method used is literature study, bibliometric analysis using VOSViewers software, and Microsoft Excel processing. The research data was obtained from metadata from Scopus with the keywords science, literacy and metacognitive and in 3,881 documents from 2016-2020, but the first 2,000 documents could be used. The research was conducted in May 2021. The discussion results show that there is still little or no research on scientific and metacognitive literacy. Thus, the topic of scientific literacy and metacognitive trends has the opportunity to be studied more deeply. Nevertheless, scientific literacy has the most significant research opportunity on issues with science education.